Triangles Are Important Here

( 2 n + 1 3 ) = ( 2 n + 2 n ) ( 2 n + 1 4 ) \large \dbinom{2n+1}3 = \dbinom{2n+2}n - \dbinom{2n+1}4

Let a > 1 a>1 and b > 1 b>1 be the two solutions satisfying the equation above. What is the value of a + b a+b ?

Notation : ( M N ) \dbinom MN denotes the binomial coefficient , ( M N ) = M ! N ! ( M N ) ! \binom MN = \dfrac{M!}{N!(M-N)!} .


The answer is 6.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Pi Han Goh
May 17, 2016

Relevant wiki: Binomial Theorem

Solving this question is equivalent to solving the equation ( 2 n + 1 3 ) + ( 2 n + 1 4 ) = ( 2 n + 2 n ) \dbinom{2n+1}3 + \dbinom{2n+1}4 = \dbinom{2n+2}n .

And by definition of binomial coefficient , ( N K ) = ( N N K ) \dbinom NK = \dbinom N{N-K} , so ( 2 n + 2 n ) = ( 2 n + 2 ( 2 n + 2 ) n ) = ( 2 n + 2 n + 2 ) \dbinom{2n+2}n = \dbinom{2n+2}{(2n+2) - n} = \dbinom{2n+2}{n+2}

Using the properties of binomial coefficients , (or more commonly known as Pascal's rule ), we have

( N K ) + ( N K + 1 ) = ( N + 1 K + 1 ) . \dbinom NK + \dbinom N{K+1} = \dbinom{N+1}{K+1} .

In this case, N = 2 n + 1 , K = 3 N = 2n+1, K = 3 , so ( 2 n + 1 3 ) + ( 2 n + 1 4 ) = ( 2 n + 2 4 ) \dbinom{2n+1}3 + \dbinom{2n+1}4 = \dbinom{2n+2}4 . Thus
( 2 n + 2 n ) = ( 2 n + 2 4 ) n = 4 \dbinom{2n+2}n = \dbinom{2n+2}4 \Rightarrow n = 4 , or
( 2 n + 2 n + 2 ) = ( 2 n + 2 4 ) n + 2 = 4 n = 2 \dbinom{2n+2}{n+2} = \dbinom{2n+2}4 \Rightarrow n+2 = 4 \Rightarrow n =2 .

Hence, the values of a a and b b are 2 and 4. And their sum is 2 + 4 = 6 2+4 =\boxed6 .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...